2008
DOI: 10.1677/erc-08-0017
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of long-term outcome in gastroenteropancreatic neuroendocrine tumours

Abstract: Neuroendocrine tumours (NET) of the gastroenteropancreatic system comprise a malignant entity with a low incidence. Only limited information is available on long-term clinical outcome and clinically applicable prognostic factors. We performed a retrospective analysis of a large, wellcharacterized centre-based patient cohort of 399 patients with histologically proven NET. Data were analysed according to epidemiological, clinical and histopathological characteristics. Detailed survival analyses using the Kaplan-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
258
5
21

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(306 citation statements)
references
References 51 publications
19
258
5
21
Order By: Relevance
“…In addition, selection of patients was based on the requisite of a pathological review and an entire follow-up in our institution since diagnosis. This figure is in the upper range of previous publications using the same restrictive inclusion criteria, which reported a 6-33% frequency of G3 NEN according to ENETS proposals (Pape et al 2008, Niederle et al 2010 Panzuto et al 2011). The highest percentages were observed in two of these series in which untreated or metastatic GEP-NEN patients were enrolled , Panzuto et al 2011.…”
Section: Discussionsupporting
confidence: 58%
“…In addition, selection of patients was based on the requisite of a pathological review and an entire follow-up in our institution since diagnosis. This figure is in the upper range of previous publications using the same restrictive inclusion criteria, which reported a 6-33% frequency of G3 NEN according to ENETS proposals (Pape et al 2008, Niederle et al 2010 Panzuto et al 2011). The highest percentages were observed in two of these series in which untreated or metastatic GEP-NEN patients were enrolled , Panzuto et al 2011.…”
Section: Discussionsupporting
confidence: 58%
“…In European and American referral centers, up to 77 and 91 % of patients with PNETs and intestinal NETs [19][20][21][22] present with distant metastases at initial diagnosis, respectively [13]. In the present Japanese study, patients in whom distant metastases were observed at initial diagnosis accounted for 19.9 % of PNETs and 6.0 % of GI-NETs.…”
Section: Discussionmentioning
confidence: 45%
“…Carcinoid syndrome has been reported to be present in 8%-35% of patients with NETs and is characterized by a wide range of symptoms, such as flushing episodes, diarrhea, abdominal pain, intermittent bronchial wheezing, telangiectasia, heart valve disease, mesenteric fibrosis, and pellagra [5,[9][10][11]. Carcinoid crisis is considered an immediate life-threatening complication of carcinoid syndrome due to a massive release of vasoactive peptides from the tumor.…”
Section: Carcinoid Syndromementioning
confidence: 99%